Buyback contract coordination in supply chain with fairness concern under demand updating. Issue 5 (28th May 2021) - Qin, Yanhong; Shao, Yunfei; Gu, Bo
ABSTRACT: This paper sets supply chain buyback contract model with retailer's complete rationality and fairness concern respectively under stochastic demand, and uses Bayesian theorem to solve retailer's two-stage order decision under demand updating, so as to analyze the influence of retailer's fairness concern on the optimal order decision and the coordination of the buyback contract. The results show that the buyback contract can always coordinate the supply chain under the same condition; both the retailer's first order quantity and total order quantity decrease with wholesale price and increase with buyback price, but the retailer's fairness-concern behavior aggravates this trend.